The Role of Vegetal Soil Cover in Flood Control - Chaturvedi, M. D. (Indian Forester, 1951)
The severity of floods in the Indo-Gangetic basin is occasioned by the striking periodicity in monsoon and its intensity in the elevated Himalayan zone. Such powerful physical forces are best counteracted not by the rigid brick and mortar but by the resilient vegetation, the luxuriant growth of which in the region most affected is no fortuitous coincidence. The vegetal cover is Nature’s device to control the forces it unleashes. In the proper management of the catchment areas of large rivers lies our best security against floods. The challenge of the millions of drops of rain can be met only by myriads of leaves.